(untitled) (Research, Society and Development, 2021)
Objectives: To map and discuss the different kinesiotherapeutic intervention protocols with exergames for muscle strength and balance in the elderly and to investigate methods for assessing balance, muscle strength and intervention time. Materials and Methods: We performed a systematic literature review between August 2019 and January 2020 at the Virtual Health Library interface, Springer, ScienceDirect and Pedro. The search considered studies published until December 2019, without language restrictions. A total of 408 records were identified. In the selection process, 17 studies met the inclusion criteria for analysis. Results: Of the 17 studies analyzed, five demonstrated that the kinesiotherapeutic exercise protocol with exergames was effective in improving balance and muscle strength in the elderly. Seven studies demonstrated the effectiveness of conventional protocols alongside exergame protocols. Five studies analyzed showed the effectiveness of the exergame when compared to the conventional protocol. The Berg balance scale and the TUG test were the most used balance assessments and only one study reported in detail how muscle strength was assessed. Most studies performed the intervention protocol over a period of 8 to 12 weeks. Conclusion: Exergame associated with a kinesiotherapy intervention protocol or physical exercise improves muscle strength and balance in the elderly.